CT cisternography in evaluation of cerebrospinal fluid rhinorrhea - (:unkn) unknown (My University, 1990)
The clinical, radiological and surgical features of 14 patients who presented with cerebrospinal fluid rhinorrhea and had undergone surgical treatment during a three-year period are given with special reference to pre-operative evaluation by CT cisternography. The merits and demerits of this technique are discussed. © 1990 Springer-Verlag.
Keywords: Cerebrospinal fluid fistula; CT cisternography; Iohexol; Rhinorrhea